Association of primary open-angle glaucoma with endothelial NO-synthase (NOS3) rs2070744 (T-786C) in a Ukrainian population (Ukrainian Journal of Ophthalmology, 2025)
Background: Endothelial dysfunction and endothelial nitric oxide-synthase (NOS3) polymorphism play an important role in the pathogenesis of glaucomatous optic neuropathy (GON) in primary open-angle glaucoma (POAG). The rs2070744 (T-786C) variant is located in the promoter of the NOS3 gene and has been shown to be promising for association with POAG.Purpose: To identify an association between POAG and the rs2070744 (T-786C) variant in the NOS3 gene in a Ukrainian population.Material and Methods: We examined 200 patients, including 153 patients (153 eyes) diagnosed with POAG (the study group) and 47 patients (47 eyes) without POAG (the control group). The study group included patients with a mean age of 65.0 ± 13.1 years and disease duration of 4.9 ± 5.3 years. Genotypes were determined by real-time polymerase chain reaction (PCR). Mutation detection and quantification were performed using TaqMan Mutation Detection Assays (Life Technologies, Carlsbad, CA). Statistical analyses were performed using Statistica 10 software (StatSoft, Tulsa, OK, USA).Results: The minor T allele of rs2070744 was associated with a 1.7-fold decreased risk of POAG (OR = 0.589; 95% CI, 0.370-0.938; p = 0.025). The ancestral C allele of rs2070744 determined the genetic susceptibility of an individual to POAG. Patient carriers of the CC genotype of rs2070744 were 13.9 years and 13.2 years, respectively, younger (p < 0.001) than patient carriers of the СТ and ТТ genotypes. In addition, patient carriers of the C allele were younger than patient carriers of the T allele (61.9 ± 14.4 years versus 69.3 ± 9.6 years; p < 0.001). Eyes of patient carriers of the TT genotype showed better perimetric visual field mean deviation (MD) and pattern standard deviation (PSD), and thicker retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC), compared to eyes of carriers of other genotypes.Conclusion: Allelic polymorphism rs2070744 in NOS3 had a protective effect against POAG, facilitating less severe manifestations and less severe progression of GON in a Ukrainian population.
Keywords: primary open-angle glaucoma; rs2070744 (T-786C) NOS3